Analisis Pemungutan Pajak Hotel Dalam Meningkatkan Penerimaan Pajak Daerah Kabupaten Samosir Masa Pandemi Covid-19 Tahun 2020 – 2021 - Triska Siallagan; Chairil Anwar Pohan (Jurnal Ilmu Administrasi Publik, 2022)
This research aims to ascertain and analyze hotel tax compliance to increase regional tax revenue in Samosir Regency during the COVID-19 pandemic. The study uses qualitative research methods with a qualitative descriptive approach. The results of this study using a SWOT analysis show that the BPKPD of Samosir Regency in collecting hotel taxes in 2020-2021 has not been effective, which in 2020 the target and realization of hotel taxes have been achieved while for 2021 it has not been achieved and is only around 76.61%. The compliance of hotel taxes in Samosir Regency can be said to have a considerable influence on raising local tax revenue, even though it has not fully contributed to local funds. Despite some of the obstacles experienced by BPKDP in collecting hotel taxes on increasing regional tax revenue for Samosir Regency during the 2020-2021 Covid-19 Pandemic, the Samosir government performs mobile service each month in each district and provide a tapping box or transaction data to increase hotel tax in reporting and pay taxes.